PERILAKU PERBERASAN DI JAWA TIMUR - WAYAN SUDANA; SUNAR SUDIONO; SUJATMO - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2002)
Rice is the most important and strategic crop. Hence, distribution, price stabilityof rice and continuous availability at market are the government should achievethe main objectives. This study was conducted at East Java province, theobjectives of this study to identify the effectively of floor price policy, factorseffecting farm gate price of rice, market structure and efficiency of rice marketing.The results of the study showed that, farm gate price of rice at harvest time (Feb-March) relatively the same with floor price. The main factor effecting of rice priceat harvest time is weather, bed weather (heavy rain) price will decrease 20 to 30percent under floor price. Market structure of rice in East Java is almostcompetitive and efficiency.